2018
DOI: 10.1007/s10461-018-2150-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations with Unprotected Sexual Behavior Among HIV-Infected Drinkers in Western Kenya

Abstract: Approximately 71% of HIV-infected individuals live in sub-Saharan Africa. Alcohol use increases unprotected sex, which can lead to HIV transmission. Little research examines risky sex among HIV-infected individuals in East Africa who are not sex workers. The study purpose was to examine associations with unprotected sex in a high-risk sample of 507 HIV-infected sexually active drinkers in western Kenya. They were enrolled in a trial to reduce alcohol use. Past-month baseline alcohol use and sexual behavior wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Another predictor found in this study was that using alcohol during sexual intercourse is 2.1 more likely to have unprotected sex with an HIV-serodifferent sexual partnership. This result is in line with several other studies in the literature that have shown the association between alcohol use and risky sexual behavior among PLHIV ( 36 - 37 ) . Among serodifferent partnerships, this behavior is particularly worrying, mainly because it exposes seronegative partners to HIV exposure.…”
Section: Discussionsupporting
confidence: 93%
“…Another predictor found in this study was that using alcohol during sexual intercourse is 2.1 more likely to have unprotected sex with an HIV-serodifferent sexual partnership. This result is in line with several other studies in the literature that have shown the association between alcohol use and risky sexual behavior among PLHIV ( 36 - 37 ) . Among serodifferent partnerships, this behavior is particularly worrying, mainly because it exposes seronegative partners to HIV exposure.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the use of condoms depends on the level of social development. All studies, known to us, not unequivocally confirming the association between alcohol drinking and non-use of condoms, were performed in more developed countries including Russia [17,[42][43][44][45][46][47][48][49][50]; while those from less developed and newly industrialized countries do generally confirm such association [51][52][53][54][55][56][57][58][59]. In the U.S. indicators of the alcohol consumption were stronger predictors of an inconsistent condom use in African Americans than in Whites [60].…”
Section: Casementioning
confidence: 99%
“…Hazardous alcohol use (HAU), defined as a pattern of alcohol consumption that increases the risk of harmful consequences for the user or others, is associated with both elevated risk of acquiring HIV and poor health outcomes among PLHIV [ 5 , 6 , 7 , 8 ]. Alcohol consumption is associated with an increased likelihood of engaging in behaviours that elevate the risk of HIV acquisition, such as decreased sexual inhibition, acts of condomless sex and multiple sexual partners [ 6 , 7 , 8 , 9 ]. In addition, excessive alcohol consumption can result in deferred testing for HIV infection, delayed linkage to ART initiation for newly diagnosed PLHIV and lower treatment adherence [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%